Declaration of peaceful education in Indonesia Higher Education - Hafifuddin, .; Zulfikar, Ali Buto; Ahmad Muhaimin, Mohamad (Universiti Malaysia Pahang, 2021)
Background and Purpose: This paper focuses on the declaration of peace education in higher education. This study was conducted in qualitative with phenomenology approach. Self acknowledgement as a member in higher education must be ready to be independence, nationalist, patriotic, tolerance, peacekeepers and socialize the peaceful education environments. Nationalism and patriotism doctrine should be implemented through subjects, students’ organization and activities of faculty and students’ residents. Methodology: Qualitative research methods namely sociology phenomenology approach was used to conduct the research process, for example, to understand the meanings of the phenomena and related concepts, theories and try to find explicate the problems characteristics of the subjects and phenomena at the research settings. The research subjects are those who are the key person in managing higher education institutions in Acheh. Findings: Higher education declaration is the common supports, agreements, and understandings between the higher education institutes and government to achieve peaceful, convenience, and to maintain the unity of The Republic of Indonesia. Contributions: Declaration made by higher education institutions for peaceful education is intended as a collective commitment to maintain, direct, guide, and create peace inside and outside campus